Biochemical Oxygen Demand (COD) performance in slow filtration technology - Júnior, Ariston da Silva Melo; Ribeiro, Kleber Aristides; Gonçalves, Estevão Stutz (Seven Editora, 2024)
Sanitary engineering is an important arm in the sustainable development of the planet. To solve the environmental problems generated by the unbridled growth of cities and production and supply systems, this branch of engineering has been studying new methodologies and creating new technologies to combat environmental pollution. One of the most worrisome areas of pollution today is with water resources. Well, there is no life without water and with that it becomes important to maintain water bodies on the planet. Faced with this challenge, sanitary engineering has been studying and developing new tools for controlling the aquatic biome, known as alternative sewage treatment systems. Among the systems that make up this follow-up is the slow filter system. Slow filters are technologies based on the use of sand and gravel of different dimensions that, when united in a single chamber, form a system that, through physicochemical processes, enables the removal of polluting agents from contaminated water. The present research used a pilot system developed at UNICAMP to analyze the parameter related to Biochemical Oxygen Demand (COD). The installed system has two conventional filters, in which there is an additional layer of activated carbon to enhance the purification process. During the study period, from August 22 to August 26, 2022, the results achieved in relation to the improvement in the COD parameter were 59.15% and 73.51%. Having that values comprise to slow filters – conventional and with additional layer of activated carbon, respectively. DOI:https://doi.org/10.56238/sevened2024.001-036